A Study on Export Performance of Dry Chillies and its Products from India - Shivashankar, K.; Banakar, Basavaraj (Indian Journal of Marketing, 2008)
Chillies are mainly traded in dried or powdered (ground) form and exported to developed countries such as USA and other Western European countries. In Karnataka Chilli (capsicum annum .L) is one of the most important commercial crops. A number of varieties are grown for the purpose of vegetables, spices, condiments, sauce and pickles. Besides, the red mature pimento pepper (C. annum) the small-fruited varieties are grown and used for their decorative purpose. The growth rates both in quantity and value of exports in dry chillies found to be increased significantly during study period (1960-61 2004-05). The growth in value of exports was higher than its quantity due to higher of unit value for the commodity. The nominal protection coefficients (NPC's) indicated that India is more competitive in the export of dry chillies owing to its suitable agro-climatic conditions and cheap labour.The United States of America (USA) and Malaysia were found to be highly loyal markets for Indian chilli as indicated by the retention of their previous shares of dry chillies exports from India by more than 39 and 41 per cents, respectively. Similarly, Srilanka was emerged as a major market for the Indian chillies.